The Image of Water in the Traditional Rituals and Folksongs of the Western Podolia - Смоляк, Олег; Смоляк, Павло; Довгань, Оксана (Tautosakos darbai, 2019)
The article provides a detailed discussion of the image of water in the traditional rituals of the Western Podolia. The synonymous representations of water are particularly numerous in the ritual calendar songs of the winter cycle. The article focuses on the sources of folklore and ethnology providing grounds for an exhaustive analysis of the water image as an inherent part of the human life.The article elucidates the importance of water in the ancient Slavic and particularly in the Ukrainian culture. The ancient Slavs have been recorded as worshiping and bringing sacrifices to the rivers, lakes, wells and springs. The most important water goddess for the Ukrainian ancestors was Dana, venerated as a bright and benevolent deity that would ensure life to all the living things. Therefore, the names of the greatest Slavic rivers derive from the word dana. Similar power is ascribed to the spring rain and thunder. Rain embodies the celestial water element, while thunder combines two life bringing principles – water and light.The analysis of the national cultural heritage primarily brings forth the importance of water in the traditional worldview of the Western Podolia. The sacramental aspects of water are prominent in numerous charms and spells, which distinctly reveal personification of water and surviving reflections of its divine quality. The broadly popular magical uses of water are interpreted on the grounds of the traditional local belief in its cleansing effect and healing abilities applied to all the surrounding objects. The consecrated Jordan water that was believed to provide powerful protection from all the evil spirits was regarded in Western Podolia as an indispensable attribute of all the healing and economical magic. In Western Podolia, as in many other ethnographic Ukrainian regions, the traditional bathing in water during the calendar winter festivities was widely practiced for the purposes of ensuring physical health. This ritual has survived until nowadays along with other contemporary traditions. According to the old Ukrainian collections of the traditional folksong texts, the notion of dunai is most frequent in the folksongs from the Western Podolia. In the lyrics of these songs the water of dunai commonly occurs in such synonymous manifestations as the water as such, as a river, as a lake, as a sea or an ocean, and as other shapes of water (rain or snow), also – as a faraway country. Symbolic representations of the dunai water are particularly frequent in the wedding songs from the Western Podolia. Water as personified passive side of creation provides typical environment for the woman to make herself ready for entering the matrimony and for ensuring the continuation of life. The mythical image of dunai is rather widespread in the traditional ballads from the Western Podolia as well. Here, the water appears as a relentless deity extending its fatal embrace to accommodate the young married couples or individual family members that have betrayed each other, or as a fast, deep and overwhelming stream that proves deadly to people. In other traditional socially engaged folksongs from the Western Podolia the image of dunai is considerably less frequent. Here, it is mostly identified with the “faraway lands” and can acquire the actual meaning of the Danube River.
Keywords: image of water; Western Podolia; folksongs; worldview; folklore collections; national culture